The GI War Against Japan: American Soldiers in Asia and the Pacific During World War II - Jose, Ricardo T. (Social Science Diliman: A Philippine Journal of Society and Change; Vol 2 No 2 (2001), 2007)
World War II has been described by some Americans as “the Good War” and many books and movies have been made depicting not only the courage and heroism, but also the gruesomeness and meaninglessness of war. Interpretations and reinterpretations have been discussed, debated and studied, with some going to the extreme. For example, one American veteran responded to the debates by writing his own book, entitling it This was My War; I’ll Remember it the way I want to. Certainly, many books have been published on the various battles, campaigns, and aspects of the War, and in particular the war against Japan. And yet, despite the volumes that have been published, there are still new angles to pursue. This book presents a new and significant approach to the war in Asia and the Pacific. As World War II was being fought, attempts on all sides were made to document it, aside from the usual official reports and documents. These involved photographs, documentaries, magazine articles and even books frequently written by journalists but also by the soldiers, sailors and airmen themselves. Historians were at the scene to document events as they happened, with an eye to writing more formal and balanced histories after the tide of battle had ebbed. In the process, the War has been depicted as a series of battles and campaigns, the names of which soon became public knowledge. In the Asia-Pacific theater, these included Bataan and Corregidor; the Battles of the Coral Sea, Midway, Leyte Gulf; the invasions of Guadalcanal, Tarawa, Leyte, Iwo Jima and Okinawa. This view of the War as a series of campaigns and battles is important and continues to be studied as the military, tactical and strategic aspects of the fighting still bring out many angles which have not been told fully.